Implementasi Algoritma First Come First Served Pada Sistem E-Booking Lapangan Dihafa Mini Soccer - Ramadhan, M Rizqi Maulana; Sarwido, Sarwido; Tamrin, Teguh (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
Dihafa Mini Soccer Field faces challenges in its manual booking process, which is prone to errors and time-consuming, leading to customer dissatisfaction and inefficiencies in schedule management. This study aims to develop an E-Booking system using the First Come First Served (FCFS) algorithm to address these issues. The system was designed using the Rapid Application Development (RAD) method, enabling fast development through iterative prototyping. System validation was conducted using the Black Box Testing method on features such as input validation and automatic scheduling. The testing results indicate that the system performs as expected, with accurate data validation and scheduling. The implementation of the FCFS algorithm ensures that bookings are processed fairly based on arrival order, improving efficiency and service quality. The average waiting time was successfully reduced to 90 minutes. This study demonstrates that an FCFS-based system provides an effective solution to enhance performance and customer satisfaction while offering a relevant model for application in other sports facilities.Keywords: E-Booking; First Come First Served; Rapid Application Development; Black Box Testing; Schedule Management.Â AbstrakLapangan Dihafa Mini Soccer menghadapi kendala dalam proses pemesanan manual yang rentan kesalahan dan membutuhkan banyak waktu. Dampaknya adalah ketidakpuasan pelanggan dan ketidakefisienan dalam pengelolaan jadwal. Penelitian ini bertujuan mengembangkan sistem E-Booking menggunakan algoritma First Come First Served (FCFS) untuk mengatasi masalah tersebut. Sistem dirancang menggunakan metode Rapid Application Development (RAD), yang memungkinkan pengembangan cepat melalui iterasi prototipe. Validasi sistem dilakukan dengan metode Black Box Testing pada fitur-fitur seperti validasi input dan penjadwalan otomatis. Hasil pengujian menunjukkan sistem berjalan sesuai ekspektasi, dengan validasi data dan penjadwalan yang akurat. Implementasi algoritma FCFS memastikan bahwa setiap pesanan dilayani secara adil berdasarkan urutan kedatangan, sehingga efisiensi dan kualitas layanan meningkat. Rata-rata waktu tunggu pengguna berhasil diturunkan hingga 90 menit. Penelitian ini menunjukkan bahwa sistem berbasis FCFS memberikan solusi efektif untuk meningkatkan kinerja dan kepuasan pelanggan, serta menawarkan model yang relevan untuk diterapkan pada fasilitas olahraga lainnya.Â